Utilização de objetos de aprendizagem como auxílio no ensino de geometria analítica - Silva, Carlos Sérgio Rodrigues da (2013)
This study seeks to analyze the efficiency of the use of learning objects in teaching analytic geometry, more precisely on subject distance between two points. For this, it was chosen an experimental study involving 14 students of the 3rd year of Primary School and Middle Senador Fernandes Távora, which is located in the neighborhood Demócrito Rocha, in the city of Fortaleza, state of Ceará. The class was divided into two groups of eight students each but two of these students did not participate in the entire study. In one of the groups was applied the activity Pontos em Batalha and the other only the traditional method. The instruments for data collection were activities rived, socioeconomic questionnaire and multiple-choice test with questions on location in the Cartesian plane and the distance between two points. Data were analyzed by means of graphical program Microsoft Excel. It was noticed as a result, the group submitted to the application of the learning object had a better performance on the test compared to the other group.